The Caregiving Responsibilities of Retirees: What Are They and How Do They Affect Retirees' Well-being? - Charlene M. Kalenkoski; Eakamon Oumtrakool (Institute for the Study of Labor (IZA), 2015)
Using data from the 2010 and 2012 American Time Use Surveys (ATUS) and the associated Well-being Modules, this paper examines how caregiving affects the well-being of retirees who are caregivers. Different caregiving activities are examined, including caring for household children, caring for non-household children, caring for household adults, and caring for non-household adults. Different aspects of well-being are examined, including how meaningful respondents find their activities and how happy, sad, tired, in pain, and stressed their activities make them. The results show that, controlling for selection into caregiving, most caregiving negatively affects the well-being of retirees. This suggests that policies that remove some of the caregiving burden from retirees would increase their well-being.
Keywords: D10; D13; 330; caregiving; well-being; retirement; time use